PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR FISIKA DI SMK NEGERI 5 JEMBER - Ade Shahnaz Ruhil; Bambang Supriadi; Lailatul Nuraini; Syamsuri Syamsuri (Saintifika, 2020)
Cooperative learning is a learning model that involves students to be able to actively participate in the learning process through the formation of small groups. One type of cooperative learning model is the Student Team Achievement Division (STAD) type. This study aimed to determine the effect of the STAD type cooperative learning model on physics learning outcomes of grade X students at SMK 5 Jember. This research is included in experimental research. The research design used was a post test only design. Data analysis technique used independent sample t-test (parametric test) and one way anova. The results showed that the significant value of the independent sample t-test was 0,000 (α<0,05) which means that the average physics scores of the experimental class students were greater than control class students. Thus, the STAD type cooperative learning model has a significant effect on learning outcomes in physics at SMK 5 Jember. Kata Kunci: cooperative learning; learning outcomes; STAD